Hydrogeochemical precursors in Kamchatka (Russia) related to the strongest earthquakes in 1988-1997 - Biagi P. F.; Cozzi E.; Khatkevich Y. M.; Gordeev E. I.; ERMINI, ANITA (KLUWER ACADEMIC PUBL, 2000)
The Kamchatka peninsula, located in the far east of Russia, is a geologically active margin where the Pacific plate subducts beneath the North American and Eurasia plates. This area is characterised by frequent and strong seismic activity (magnitudes up to 8.5) and epicentres are generally distributed offshore along the eastern coast of the peninsula. For many years, hydrogeochemicals have been collected with a mean sampling frequency of three days in the form of the flow rate and the most common ions and gases in the groundwater of three deep wells in the southern area of the Kamchatka peninsula, where the capital city Petropavlovsk is located. Beginning in 1988, five earthquakes with M > 6.5 occurred in this area. These earthquakes were powerful enough to be considered as potential precursor sources in the sense that the stresses and strains building up before them might be expected to cause precursory activity. In order to reveal any possible precursors of these earthquakes, we analysed the hydrogeochemical data collected. We considered any signal having an amplitude three times the standard deviation to be an irregularity and we defined as an anomaly the existence of an irregularity occurring simultaneously in more than one parameter at each well. Then, on the basis of the worldwide past results and the time recurrence of the quoted earthquakes, we chose 158 days as the maximum temporal window between a possible anomaly and the subsequent earthquake. We identified some premonitory anomalies in hydrogeochemical parameters at different wells. On the basis of these results some earthquake forecasting criteria in southern Kamchatka may be tentatively formulated.